Penerapan E-Government dalam Pelayanan Perizinan Online melalui “SIMPONIE” di DPMPTSP Kabupaten Serang - Gea Tamara; Agus Widiyarta (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
The emergence of demands from the public for public services, encourages the existing central and local governments to use information technology in the implementation of public services known as e-government. One of the regional government that utilizes e-government in providing public services, especially licensing services, is the DPMPTSP Serang Regency which is currently carried out online through SIMPONIE. This study aims to analyze the implementation of e-government in online licensing services through SIMPONIE in DPMPTSP Serang Regency. The research method in this study uses qualitative with a descriptive approach. Data collection techniques in the form of interviews, observations, and documentation. The theory used in this research is a successful element of implementation e-government based on the results of studies and research of the Harvard JFK School of Government, including support, capacity, and value. The results of the study show that the implementation of SIMPONIE in the DPMPTSP Serang Regency can be said to be a success. This can be seen from the support in the form of vision and mission, regulations, and socialization. The implementation of SIMPONIE also provides benefits such as easier service and does not take a long time, it's just that in its implementation there are still network constraints that make SIMPONIE sometimes inaccessible.